The Relationship Between PSA and Total Testosterone Levels in Men with Prostate Cancer. Issue 3 (9th February 2022) - Flores, Jose M; Bernie, Helen L; Miranda, Eduardo; Nascimento, Bruno; Schofield, Elizabeth; Benfante, Nicole; Carlsson, Sigrid; Mulhall, John P.
ABSTRACT: Background: Prostate-specific antigen (PSA) secretion is a testosterone (T) dependent process. Published data suggest that a low T level is an independent predictor of higher-grade prostate cancer (PC). Aim: To evaluate the relationship between T and PSA in patients with PC. Methods: All men diagnosed with PC with a recorded pre-treatment total T level measurement were included in this analysis. We analyzed demographic, clinical, and pathological data. Patients were stratified according to pretreatment PSA levels: <2 ng/mL, 2–4 ng/mL, >4 ng/mL. Low T was defined as total T < 10.4 nmol/L (300 ng/dL), very low T < 6.9 nmol/L (200 ng/dL). Outcomes: T levels by PSA groups according to the PC pathology. Results: In this retrospective study, mean patient age was 61 years among 646 men. The distribution by PSA group was: 8% (<2), 17% (2–4), and 76% (>4). The mean T level across the entire cohort was 13 nmol/L (374 ng/dL). Overall, 30% had a T level < 10.4 nmol/L (300 ng/dL). The mean total T level by PSA group was: <2 ng/mL, 7 nmol/L (206 ng/dL); 2–4 ng/mL, 13 nmol/L (362 ng/dL); >4 ng/mL, 14 nmol/L (393 ng/dL), P < .001. PSA <4 ng/mL was a significant predictor of low T in men with PC GS ≥8. PSA <2 ng/mL was a significant predictor of very low T independent of the PC pathology. Clinical Implications: These findings suggest that clinicians should consider measuring T levels when a patient diagnosed with PC GS ≥8 and PSA level <4 ng/mL, and for each patient with PSA level <2 ng/mL independent of the PC pathology. Strengths & Limitations: Our study has several strengths including (i) inclusion of a large population of men, (ii) use of a database which is audited and reviewed for accuracy annually, and (iii) use of an accurate T assay (LCMS). Nonetheless, there are limitations: (i) the subjects of the study are from a single institution, and (ii) we did not measure free T levels. Conclusion: In men with PC with GS ≥8, PSA level <4 ng/mL predicts low T. PSA <2 ng/mL predicts very low T independent of the PC pathology.